THE PREDICTIVE POWER BETWEEN IL28B GENE VARIANTS (RS12979860 AND RS8099917) AND THE RESPONSE OF HEPATITIS C VIRUS IN PATIENTS ON SOFOSBUVIR AND DACLATASVIR. - Dr. Mohsina Haq; Dr. Jawad Ahmed; Dr. Ihsan Ullah; Dr Hala Rajab; Dr. Sami Siraj; Dr. Najeeb ul Haq; Dr. Abbas Saleem Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Hepatitis C virus (HCV) is a serious global health hazard with an estimated 71 million individuals chronically infected. Out of them, 20% may afterward develop liver cirrhosis, and 5% of the individuals with liver cirrhosis will develop hepatocellular carcinoma. IL-28B, along with IL28A and 29, represents a cluster located on chromosome 19. IL-28B stores the information needed to encode interferon lambda 3 (INF-λ3). INF-λ3 along with INF-λ1 and INF-λ2 are type 3 interferons and play a vital role in viral infections. Objective: To identify polymorphisms occurring in IL28B genes rs12979860 and rs8099917 in patients resistant to combination therapy (SOF + DCV) and patients responding to   (SOF+DCV).Methodology: In the study, twelve diagnosed hepatitis C genotype 3 patients were taken. They were divided into two groups. Each group had six patients. One group was the treatment responder group. These patients were diagnosed as HCV patients, but their treatment had not started at the time of sampling. The other group of patients was the treatment-resistant group. These patients did not respond to two direct antiviral agents, i.e., Sofosbuvir and Daclatasvir, after 12 weeks and did not achieve a good end-treatment response. From each patient, 5cc of blood was derived and stored in an EDTA tube for IL28B analysis and a gel tube for cDNA synthesis. Samples were stored at -80C for Polymerase chain reaction and Sanger Sequencing,Results: Among the 12 patients, rs12979860 was not detected, while rs8099917 (c.252 T > G) was observed in 7 patients, and rs8113007 (c.190 A > T) in 9 patients by chance. ALT and PCR viral load levels significantly decreased from baseline to the 84th day, indicating biochemical improvement in all patients. TG genotype of rs8099917 was more dominant then genotype TT in resistant group,  and in rs8113007 genotype AT was more dominant in resistant patients as compared to genotype AA.Conclusion: There was no significant association between genotypes and the treatment outcome, based on the change in ALT levels and the PCR viral loads both before and post-treatment. The polymorphisms studied does not have a strong effect on the outcome or treatment failure in the considered population.